ASSISTANCE FOR REVITALIZATION OF KELAPA LIMA BEACH AREA BASED ON RELIGIOUS MODERATION AS A TOURISM CENTER AND PEACE BUILDING FOR THE PAPUTUNGAN COMMUNITY - ARIF RAHMAN HAKIM; Irwan Ramadhani; Khoirun Nikmah; Amir Mukminin (Jurnal Al Basirah, 2022)
Kelapa Lima Beach, which is located in Paputungan Village, West Likupang, North Minahasa, is a natural asset of the village on the sea coast. However, over time the name Kelapa Lima Beach began to dim even the generation of the 90s and below did not know the name of the beach owned by this village. So, people just call it Pante Muka. This beach, which has the beauty of dusk, used to be the center of the crowd, but now it is only as a boat stopover. This is because the social community is divided due to the construction of a hotel area by PT Bhineka Mancwisata on community land which he said had been purchased in the 90s. Therefore, the existence of KKN Nusantara students who carry out the strengthening of religious moderation can provide a way out in the midst of the community's perspective on this conflict. Students jumped in bringing the ABCD method whose emphasis is on asset development. Departing from this beach asset which is based on the longing of the community, students make students revitalize the beach. After this activity was carried out, the community again enlivened the vicinity of the beach. In fact, this indirectly supports the program of the tourism awareness group that is the core group of students in carrying out their work. This result can open up people's views regarding the potential assets owned. Later, the Kelapa Lima Beach area can become a tourism center that can grow the economy of the village community.